Search for associated production of a Z boson with an invisibly decaying Higgs boson or dark matter candidates at √s=13 TeV with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Krishnan, Anjali; Mkrtchyan, Tigran; Napolitano, Fabrizio; et al. (Physics letters, 2022)
A search for invisible decays of the Higgs boson as well as searches for dark matter candidates, produced together with a leptonically decaying Z boson, are presented. The analysis is performed using proton−proton collisions at a centre-of-mass energy of 13 TeV, delivered by the LHC, corresponding to an integrated luminosity of 139fb−1 and recorded by the ATLAS experiment. Assuming Standard Model cross-sections for ZH production, the observed (expected) upper limit on the branching ratio of the Higgs boson to invisible particles is found to be 19% (19%) at the 95% confidence level. Exclusion limits are also set for simplified dark matter models and two-Higgs-doublet models with an additional pseudoscalar mediator.
Im Titel steht der Buchstabe s unter dem Wurzelzeichen
Gesehen am 25.08.2022
ATLAS Collaboration: G. Aad, L.M. Baltes, F. Bartels, F.L. Castillo, M.M. Czurylo, S.J. Dittmeier, M. Dunford, S. Franchino, M. Klassen, A. Krishnan, T. Mkrtchyan, F. Napolitano, P.S. Ott, D.F. Rassloff, S. Rodriguez Bosca, C. Sauer, A. Schoening, H-C. Schultz-Coulon, T.M. Spieker, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, X. Yue, J. Zinsser [und 2885 weitere]